Analysis of stereotactic biopsies for nonpalpable BIRADS 4 breast lesions: Evaluation of predictors for malignancy (Annals of Medical Research, 2021)
Aim: This study aims to determine the malignancy rates of nonpalpable BIRADS 4 breast lesions excised by stereotactic biopsy, the re-excision rates of malignant lesions detected by stereotactic biopsy and to evaluate the factors affecting malignancy rates in these lesions.Materials and Methods: Medical records of female patients admitted to the surgical oncology outpatient clinic between 2012 and 2017 with nonpalpable (